'Benefits broods': The cultural and political crafting of anti-welfare commonsense. (November 2015) - Jensen, Tracey; Tyler, Imogen
In the aftermath of the global banking crises, a political economy of permanent state austerity has emerged, driven by and legitimated through a hardening anti-welfare commonsense. We argue that, while there is an excellent evidence base emerging around solidifying negative public attitudes towards welfare, critical policy studies needs to attend to the cultural as well as the political economies through which an anti-welfare commonsense is formed and legitimated. We adopt a 'cultural political economy' approach to examine the cultural and political crafting of 'benefit brood' families within the wider public sphere, to examine the mechanisms through which anti-welfare sentiments are produced and mediated. Through a case study of Mick Philpott, we demonstrate how 'benefits broods' operate both as technologies of control (through which to manage precariat populations), but also as technologies of consent through which a wider and deeper anti-welfare commonsense is effected.